THE INFLUENCE OF LEADERSHIP STYLE ON THE WORK MOREST OF EMPLOYEES AT THE OFFICE OF MANPOWER AND TRANSMIGRATION OFFICE GOWA DISTRICT - Muh. Alfian; Edi Jusriadi; Asri Jaya (CV. AFDIFAL MAJU BERKAH, 2024)
The purpose of this research is a type of quantitative research with the aim of knowing the effect of leadership style on work enthusiasm in the Office of Manpower and Transmigration, Gowa Regency. This sample was taken from the office of the Office of Manpower and Transmigration, Gowa Regency. The type of data used in this study is quantitative data obtained from questionnaires distributed and related to the problem under study. The research method used in this study is quantitative data obtained from questionnaires that are distributed related to the problem under study. Data collection techniques used are observation, questionnaires, and documentation. In this study, the data sources used in data collection include primary data and secondary data. The research instrument used in this study used the Likert scale method. And the data analysis technique used is descriptive analysis, instrument testing, and hypothesis testing. Based on the results of data research using statistical calculations through the Statistical Package for the Social Science (SPSS) version 23 application regarding the effect of leadership style on employee morale at the Gowa Regency Manpower and Transmigration Office, it shows that there is a low influence between leadership style on employee morale at the Gowa Regency Manpower and Transmigration Office, obtained ttable = 1.697, while tcount = -1.508, it can be concluded that tcount is smaller than ttable, so the hypothesis proposed is not proven, which means rejecting the alternative hypothesis (Ha) and accepting the null hypothesis (Ho ) because the correlation is